DIAGNOSTIC AND PROPOSAL OF RECOVERY OF THE LAKE MANACÁS WATERSHED, CAMPUS OF THE FEDERAL UNIVERSITY OF JUIZ DE FORA, MINAS GERAIS - Sarah Lawall; Fillipe Tamiozzo Pereira Torres; Geraldo César Rocha (Sociedade & Natureza)
The world environmental degradation, and specifically, the third world degradation, hasbecome an issue of magnifying concern. In searching of development, rural and urban areasare becoming highly affected, both in biotic and physical terms. One can observe severalexamples of bad use of water and soil resources. Impacts as soil erosion and compaction,desertification, sedimentation and water contamination are common aspects in Brazil,pointing to the urgency of multidisciplinar actions targeting to the establishment ofenvironmental equilibrium and sustentability conditions (DIAS & GRIFFITH, 1988).Inside this environmental scenario there is the recuperation of degraded areas, important topicof the sustainable development. Since the beginnings of the 1980 decade, with thedevelopment of the ecology of restoration as a science, the researchers have focusing moreprecisely on this theme (KAGEYAMA, 2003). In Brazil, the law only demands recuperationactions in the mining activities. But, in recent years, the literature shows an increasing interestabout the impacts of agriculture, engineering and inadequate occupation of urban areas. DIAS& GRIFFITH (op cit) define the recuperation of degraded areas as a assemblage of actionstargeting to reestablish the initial environmental conditions of equilibrium and sustentabilityof that areas.In this way, the objective of this work is to propose a plane of recuperation of the ManacásLake watershed, a system highly impacted and located at the campus of the FederalUniversity of Juiz de Fora, Minas Gerais state, in Brazil.